Änderungen des Strahlstroms und die Folgen - Dethloff, Klaus (Wissenschaftliche Auswertungen in Kooperation mit GEO Magazin, Hamburg, 2024)
Changes in the jet stream and the consequences: In the winters of the last four decades, the zonal flow in the atmosphere weakened over the mid-latitudes and strengthened in the subtropics. The decrease in the zonal velocity in the jet stream is associated with an increase in the meridional wind component, stronger planetary waves and the formation of a central European high pressure situation. The above-average warming of the surface and lower atmosphere in the Arctic reduces the meridional temperature gradient and thus the baroclinicity of the lower troposphere, which shifts the trajectories of the low-pressure areas towards the equator. However, the average global warming also warms the upper tropical troposphere more than the surface, and cools the lower stratosphere in the Arctic, which increases the meridional temperature gradient and thus the baroclinicity, and shifts the trajectories polewards. Both effects together lead to a moderate poleward shift of the jet stream. The changes in the trajectories of the mid-latitude low-pressure areas are determined by a complicated network of surface warming, baroclinic instability, interactions with planetary waves and altered patterns of teleconnections such as the Arctic Oscillation, and are therefore very uncertain. The resulting changes in precipitation are even less certain, as they are also influenced by microphysical processes in the clouds, aerosols and changes in convection.